The effectiveness of mind mapping strategy for teaching science in the achievement of fifth grade students (Journal of the College of Basic Education, 2022)
The current research aims to identify the effectiveness of the mind mapping strategy for teaching science in the achievement of fifth grade students, and the research objective was verified by verifying the following null hypothesis: (There is no statistically significant difference at the level (0.05) between the average scores of the experimental group who study using the mental mapping strategy and the average scores of the control group who study using the traditional method in the achievement test). The research community represented all the primary schools in the General Directorate of Education of Baghdad Governorate / Al-Karkh Third, and the El-Farha Elementary School was chosen, which was intentionally chosen from the schools affiliated to the General Directorate of Education of Baghdad Governorate / Al-Karkh Third, the number of its students (120) students, all students in the fifth grade, by Three divisions (A, B, and C), and two divisions were chosen by simple random sampling, and Division (B) was the control group that studied in the traditional way and Division (C) was the experimental group that studied using mental maps, as the research sample amounted to (80) students divided into two divisions. (B, C) For each class (40) students, and the failing students were excluded, the two groups were rewarded with the variables (intelligence, previous achievement in science). In order to verify the research objective, a post-achievement test was prepared that included (20) objective paragraphs of a multiple-choice type with four alternatives, and verified its apparent validity and content, and the stability was extracted using the Keoder-Richardson equation -20, which amounted to (0.89), as the psychometric properties of its paragraphs were extracted. In terms of ease, difficulty, discriminatory strength, and effectiveness of alternatives, the experiment was applied at the beginning of the first semester of the academic year (2021-2022), and lasted (8) weeks. After the completion of the experiment, the data were statistically treated using the T-test equation for two independent samples of different numbers. The results showed that the members of the experimental group outperformed their peers in the control group with statistical significance in the achievement test, Therefore, the researcher recommends some recommendations and suggestions using the mind mapping strategy for the fifth grade of primary school, and suggests conducting other studies for different subjects and stages of study.